Dynamic Meta Modelling: A Graphical Approach to Operational Semantics - Engels, Gregor; Heckel, Reiko; Sauer, Stefan (Proceedings of the workshop on Rigorous Modeling and Analysis with the UML: Challenges and Limitations (satellite event of the Conference on Onject-Oriented Programming, Systems, Languages, and Applications (OOPSLA 1999)), Denver, CO (USA))
In this paper, dynamic meta modeling is proposed as a new approach to the operational semantics of behavioral UML diagrams. The dynamic meta model extends the well-known static meta model by a specification of the system’s dynamics by means of collaboration diagrams. In this way, it is possible to define the behavior of UML diagrams within UML. The conceptual idea is inherited from Plotkin’s structured operational semantics (SOS) paradigm, a style of semantics specification for concurrent programming languages and process calculi: Collaboration diagrams are used as deduction rules to specify a goal-oriented interpreter for the language. The approach is exemplified using a fragment of UML statechart and object diagrams. Formally, collaboration diagrams are interpreted as graph transformation rules. In this way, dynamic UML semantics can be both mathematically rigorous so as to enable formal specifications and proofs and, due to the use of UML notation, understandable without prior knowledge of heavy mathematic machinery. Thus, it can be used as a reference by tool developers, teachers, and advanced users.

MVC-Based Modeling Support for Embedded Real-Time Systems - Engels, Gregor; Sauer, Stefan (Proceedings of OMER Workshop, Herrsching, Germany)
Several software architecture paradigms have been proposed for the development of interactive software systems and applications. Their common idea is the separation of user interface components from application logic. Normally, they are deployed as design patterns or basic frameworks of interactive systems. Deploying these architecture paradigms for multimedia systems or embedded real-time systems, first requires an appropriate adaption to the specific aspects of these application areas. We will compare within this position paper two well-known architecture paradigms and motivate an advanced architecture paradigm applicable to real-time, embedded multimedia systems. In addition, we will discuss that the architecture paradigm should be reflected within the structure of a modeling language.

An Assessment of Aspect Language Design - Mehner, Katharina; Wagner, Annika (Proceedings of the Young Researchers Workshop (satellite event of the Generative and Component-Based Software Engineering (GCSE 1999)), Erfurt (Germany))

On the Role of Method Families in Aspect Oriented Programming - Mehner, Katharina; Wagner, Annika (Proceedings of the ECOOP Workshop on Aspect Oriented Programming, Lisboa (Spain))

Ein Vorgehensmodell für die Multimedia-Entwicklung mit Autorensystemen - Depke, Ralph; Engels, Gregor; Mehner, Katharina; Sauer, Stefan; Wagner, Annika (Informatik Forschung und Entwicklung)
Multimedia-Anwendungen sind interaktive Softwaresysteme und verlangen als solche, mit softwaretechnischen Methoden erstellt zu werden. Sie werden heutzutage in der Regel mit Hilfe von Autorensystemen entwickelt, die eine Ad-hoc-Entwicklung auf Implementierungsniveau unterstützen. Hierdurch und wegen des Fehlens etablierter Vorgehensmodelle für die Multimedia-Softwareentwicklung reduziert sich der Multimedia-Entwicklungsprozeß auf die Implementierungsphase. Dies führt zu den in der Softwaretechnik bekannten Problemen wie mangelnder Konzeption und fehlender Dokumentation. Wir stellen in diesem Beitrag ein Vorgehensmodell für die Entwicklung von Multimedia-Anwendungen vor, in dessen Mittelpunkt eine Analyse- und Entwurfsphase im Hinblick auf eine Implementierung der Multimedia-Anwendung mit einem Autorensystem stehen. Ausgehend von einem frameworkbasierten Analysemodell der Anwendung und einem Modell der Realisierungsmöglichkeiten mit einem konkreten Autorensystem wird systematisch ein Implementierungsmodell auf Instanzebene abgeleitet, das als Eingabe für das Autorensystem verwendet wird. Das postulierte Vorgehensmodell wird exemplarisch für das Autorensystem Director am Beispiel der Domäne multimedialer Lehr-/Lernanwendungen erläutert.

Formalization of the development process for a software-hardware reflexodiagnostic tool - Cherchago, Alexey; Finaev, V. (Scientific bulletin of Academy of Information Technologies in Education, Science and Balneology)

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele (Science of Computer Programming)
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, to a single computational paradigm. In this paper we present some recent developments in applying graph transformations as a rule-based framework for the specification and development of systems, languages, and tools. After reviewing the basic features of graph transformation, we discuss a selection of applications, including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification of abstract data types, and the definition of a visual database query language. The case studies indicate the need for suitable structuring principles which are independent of a particular graph transformation approach. To this end, we present the concept of a transformation unit, which allows systematic and structured specifications and programming based on graph transformation.

Handbook of Graph Grammars and Computing by Graph Transformation: Vol. 2: Applications, Languages, and Tools - Ehrig, Hartmut; Engels, Gregor; Kreowski, Hans Jörg; Rozenberg, Grzegorz
Graph grammars originated in the late 60s, motivated by considerations about pattern recognition and compiler construction. Since then, the list of areas which have interacted with the development of graph grammars has grown quite impressively. Besides the aforementioned areas, it includes software specification and development, VLSI layout schemes, database design, modeling of concurrent systems, massively parallel computer architectures, logic programming, computer animation, developmental biology, music composition, visual languages, and many others. The area of graph grammars and graph transformations generalizes formal language theory based on strings and the theory of term rewriting based on trees. As a matter of fact, within the area of graph grammars, graph transformation is considered as a fundamental computation paradigm where computation includes specification, programming, and implementation. Over the last three decades, graph grammars have developed at a steady pace into a theoretically attractive and important-for-applications research field. Volume 2 of the indispensable Handbook of Graph Grammars and Computing by Graph Transformations considers applications to functional languages, visual and object-oriented languages, software engineering, mechanical engineering, chemical process engineering, and images. It also presents implemented specification languages and tools, and structuring and modularization concepts for specification languages. The contributions have been written in a tutorial/survey style by the top experts in the corresponding areas. This volume is accompanied by a CD-Rom containing implementations of specification environments based on graph transformation systems, and tools whose implementation is based on the use of graph transformation systems.

A View-based Approach to System Modeling Based on Open Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this chapter we present a specification technique based on open graph transformation systems (in the double-pushout approach) by a new loose semantics for rule-based systems, which allows to model the interaction between different views, and by explicit frame conditions which restrict these interactions to an interface of open types. On this background, formal notions of view and view relation are developed and the behavior of views is described by the loose semantics. Based on the assumption that dependencies between different views are faithfully described by a common reference model, a construction is developed for the automatic integration of views. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of banking system.

Classification and Comparison of Module Concepts for Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
In this chapter we use a three-level approach for analyzing module concepts for graph transformation systems. Based on the observation that module architectures consist of basic specications like body or export interface and relations like the implementation relation between them, or the import relation between a client and a server module, module concepts are characterized by answering the questions 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to module architectures? These three questions are investigated for five module concepts available in the literature. As a reference example, a samplemodular specification of resource management in distributed operating systems is presented.

Semi-Formal and Formal Specification Techniques
During the last 20 years several different formal and semi-formal specification techniques have been successfully developed and used. Applications comprise the specification of simple programs, data types and processes as well as complex hardware and software systems. The variety of specification techniques ranges from formal set theoretical, algebraic, and logic approaches for specifying sequential systems and from Petri-nets, process algebras, automata, and graph grammars for specifying concurrent and distributed behaviors to semi-formal software engineering methods for developing complex systems. Formal and semi-formal approaches have their advantages and disadvantages: the informal diagrammatic methods are easier to understand and to apply but they can be ambiguous. Due to the different nature of the employed diagrams and descriptions it is often difficult to get a comprehensive view of all functional and dynamic properties. On the other hand, the formal approaches are more difficult to learn and require mathematical training. But they provide mathematical rigor for analysis and prototyping of designs. Verification is possible only with formal techniques. Since a few years many researchers and research groups are putting more and more effort in closing this gap by integrating semi-formal and formal specification techniques. Their studies and experiences show the added value of combining semi-formal and formal techniques and at the same time open a whole range of new problems and questions which cannot be asked when studying formalisms in isolation. In this seminar more than 40 scientists came together in 28 talks and two panel discussions to study possibilities and solutions for integrating and validating different formal and semi-formal specification techniques. Similarities and differences of formal and semi-formal specification formalisms as well as possibilities for combining such techniques were discussed. Most talks of this seminar analysed, compared, or integrated at least two such methods. On behalf of all participants the organizers would like to thank the staff of Schloss Dagstuhl for providing an excellent environment to the conference. The support of the TMR programme of the European Community is gratefully acknowledged. Due to this programme it was possible to fund the participation of several young researchers and of three key note speakers.

6th International Workshop on Theory and Applications of Graph Transformations (TAGT '98), Paderborn, Selected Papers

Ein Ansatz zur Verbesserung des Entwicklungsprozesses von Multimedia-Anwendungen - Depke, Ralph; Engels, Gregor; Mehner, Katharina; Sauer, Stefan; Wagner, Annika (Proceedings of the GI-Fachtagung on Softwaretechnik (1998), Paderborn (Germany))

Integration of Single Pushout Transformation and Functional Programming - Didrich, Klaus; Wagner, Annika (Proceedings of the World Conference on Integrated Design and Process Technology (IDPT 1998), Berlin (Germany))

A generalized schema of a decision-making process of a SCENAR-therapeutist - Cherchago, Alexey (Proceedings of the Scientific and Technical Conference on Medical Information Systems (MIS 1998), Taganrog (Russia))

Compositional Verification of Reactive Systems Specified by Graph Transformation - Heckel, Reiko (Proceedgins of the First International Conference on Fundamental Approaches to Software Engineering (FASE 1998), Lisbon (Portugal))

Interoperability in Train Control Systems: Specification of Scenarios Using Open Nets - Padberg, Julia; Jansen, Lars; Heckel, Reiko; Ehrig, Hartmut (Proceedings of the conference on Integrated Design and Process Technology (IDPT 1998), Berlin (Germany))

Electronic Commerce Systeme als Anwendungsbeispiel für Evolutionstechniken - Engels, Gregor; Kolmschlag, Silvia

Unterstützung der Flexibilität eines Electronic Commerce Systems durch Evolutionstechniken - Kolmschlag, Silvia; Engels, Gregor (Proceedings of the workshop on "Integration heterogener Softwaresysteme" (satellite event of the GI-Jahrestagung Informatik 1998), Magdeburg (Germany))

Structured Transition Systems as Lax Coalgebras - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Proceedings of the First Workshop on Coalgebraic Methods in Computer Science (CMCS 1998), Lisbon (Portugal))

Simple Modules for Grace - Heckel, Reiko; Hoffmann, Berthold; Knirsch, Peter; Kuske, Sabine (Selected papers of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Graph Transformation and Other Rule-Based Formalisms with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Padberg, Julia; Rozenberg, Grzegorz (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))
A general framework is presented for extending graph transformation and other rule-based formalisms in such a way that transformations with incomplete information can be handled. This extension is motivated by the need to model the behaviour of open systems in different application areas using graph transformations and Petri nets. The following two problems are central within this general framework. 1. Characterization of transformations with incomplete information. 2. Recovery of information from incomplete transformations. A solution for these problems is presented for algebraic graph transformations and Petri nets using the new concepts of graph transitions based on double pullbacks and open nets based on autonomous actions for open places. Moreover, the problems are discussed for DNA-computing and other rule-based formalisms.

Double-Pullback Graph Transitions: A Rule-Based Framework with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando; Padberg, Julia; Rozenberg, Grzegorz (Selected papers from the 6th International Workshop on Theory and Application of Graph Transformations (TAGT 1998), Paderborn (Germany))

Classification and Comparison of Modularity Concepts for Graph Transformation Systems - Ehrig, Hartmut; Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele (Pre-Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT '98), Paderborn (Germany))
This paper presents a systematic approach for classifying and comparing modularity concepts that have been proposed for graph transformation systems. The approach is based on the following observation: Modules and module interconnections consist of basic specifications (forming, e.g., a module's body, import, or export interface), and relations between such specifications, like the implementation relation between export and body of a module. Hence, a natural approach for characterizing a module concept is to answer the following three questions: 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to modules and interconnections? In this paper, these questions are considered in some detail for the following module concepts for graph transformation systems.

Model Checking Graph-Interpreted Temporal Formulas - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

DPO Derivations via Disconnected Rules - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Event Processing in Mobile and Active Database Systems Using Broadcasts - Sauer, Stefan; Zukunft, Olaf (Proceedings of the 9th International Workshop on Database and Expert Systems Applications (DEXA 1998), Vienna (Austria))
The integration of active database technology into mobile database systems allows to limit the transfer of data between mobile computers and the stationary network. In order to employ such active database mechanisms, the rule processing component of traditional active database systems needs to be modified. This paper introduces a new model for event processing and presents a new algorithm for the composition of complex events in a mobile database environment. Furthermore, the model also takes into account the possibility of broadcast data. To validate the feasibility of the model, a prototype has been built using object-oriented technology.

Construction and Characterisation of Double-Pullback Graph Transitions - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Open Graph Transformation Systems: A New Approach to the Compositional Modelling of Concurrent and Reactive Systems - Heckel, Reiko

Themenheft: Softwaretechnik

A View-Oriented Approach to System Modelling Using Graph Transformations - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Proceedings European Software Engineering Conference (ESEC 1997), Zürich (Switzerland))
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations supports an intuitive understanding and an integration of static and dynamic aspects on a well-defined semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. We define a construction for automatic view integration which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of a banking system.

Thermooptische Effekte in Nd:YAG-Slablasern - Depke, Ralph; Knoke, Stefan; Schöne, Wolfram; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft)
Vorteile von Laserkristallen in Slab-Geometrie gegenüber Stäben liegen in einer Reduktion der thermisch induzierten Linsenwirkung und der spannungsinduzierten Depolarisation durch einen zick-zack-förmigen Strahlverlauf innerhalb des Kristalls. Durch die Analyse der durch die Anordnung der Pumpquellen und die Dotierungskonzentration bestimmten Temperatur- und Spannungsverteilungen mit Hilfe eines Finite-Element-Modells und die Berechnung der resultierenden optischen Eigenschaften lassen sich die genannten Zielgrößen optimieren. Die Verfahren wurden auf am Laser Zentrum Hannover e.V. entwickelte Nd:YAG-Stab- und Slablaser angewandt und ermöglichten die Entwicklung diodengepumpter Festkörperlaser-Systeme mit Ausgangsleistungen von mehr als 750W bei guter Strahlqualität. Modellerweiterungen unter Berücksichtigung der Wechselwirkung zwischen Lasermoden und aktivem Material werden diskutiert. Diese Arbeit wird gefördert durch das BMBF, FKZ: 13 N 6361

Integrating the Specification Techniques of Graph Transformation and Temporal Logic - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea (Proceedings of the 22nd International Symposium on Mathematical Foundations of Computer Science (MFCS 1997), Bratislava (Slovakia))

Einfrequenzbetrieb von Nd:YAG-Stablasersystemen hoher Ausgangsleistung - Knoke, Stefan; Depke, Ralph; Schöne, Wolfram; Brozek, O.S.; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft, Weinheim (Germany))

Loose Semantics and Constraints for Graph Transformation Systems - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea

A 2-Categorical Presentation of Distributed Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Combining Graph Transformations with Temporal Logic - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

An Inductive View of Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the 12th International Workshop on Recent Trends in Algebraic Development Techniques (WADT 1997), Tarquinia (Italy))

Compositional Development and Verification of Graph Transformation Systems Based on Views and View Integration - Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Guest Editors' Introduction - Engels, Gregor; Jürgen Schneider, Hans (International Journal on Software Engineering and Knowledge Engineering (IJSEKE))

A Combined Reference Model- and View-Based Approach to System Specification - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Int. Journal of Software and Knowledge Engeneering)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations allows to satisfy the general requirements of an intuitive understanding and the integration of static and dynamic aspects on a well-defined and sound semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. View relations are shown to preserve the behaviour of views. Moreover, we define a construction for the automatic integration of views which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. In case of more than two views more general scenarios are developed and discussed. We are able to show that the automatic view integration is compatible with the loose semantics, i.e., the behaviour of the system model is exactly the integration of the behaviours of the views. All concepts and results are illustrated at the well-known example of a banking system.

Algebraic Approaches to Graph Transformation, Part II: Single Pushout Approach and Comparison with Double Pushout Approach - Ehrig, Hartmut; Heckel, Reiko; Korff, Martin; Löwe, Michael; Ribeiro, Leila; Wagner, Annika; Corradini, Andrea (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs corresponding to pushouts in suitable categories of graphs and graph morphisms. This allows one to give not only an explicit algebraic or set theoretical description of the constructions but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In the previous chapter we have presented an overview of the basic notions and problems common to the two algebraic approaches the double pushout DPO approach and the single pushout SPO approach and their solutions in the DPO approach. In this chapter we introduce the SPO approach to graph transformation and some of its main results. We study application conditions for graph productions and the transformation of more general structures than graphs in the SPO approach where similar generalizations have been or could be studied also in the DPO approach. Finally we present a detailed comparison of the DPO and the SPO approach especially concerning the solutions to the problems discussed for both approaches in the previous chapter.

How to represent a visual specification - Engels, Gregor; Rekers, Jan; Andries, Marc (Visual Language Theory)

Algebraic Approaches to Graph Transformation, Part I: Basic Concepts and Double Pushout Approach - Corradini, Andrea; Montanari, Ugo; Rossi, Francesca; Ehrig, Hartmut; Heckel, Reiko; Löwe, Michael (Handbook of Graph Grammars and Computing by Graph Transformation, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs, modelled by pushouts in suitable categories of graphs and graph morphisms. This allows one not only to give an explicit algebraic or set theoretical description of the constructions, but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In this chapter we start with an overwiev of the basic notions common to the two algebraic approaches, the double-pushout (DPO) approach and the singlepushout (SPO) approach; next we present the classical theory and some recent development of the double-pushout approach. The next chapter is devoted instead to the single-pushout approach, and it is closed by a comparison between the two approaches.

Special Issue on Graph Transformations

Synchronization of Views and Loose Semantics of Typed Graph Productions - Ehrig, Hartmut; Heckel, Reiko; Padberg, Julia; Taentzer, Gabriele; Wolter, Uwe; Corradini, Andrea; Engels, Gregor (Report on the Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)
The concept of views is used on two levels. First, so-called design views are developed for structuring specifications, that is, a system is modeled according to different views (e.g., representing the needs of different kinds of users) which have to be synchronized afterwards in order to build the whole system. Views can be specified by means of typed graph transformation systems, where the type graph determines the visible types and the productions describe the known operations of that view. The synchronization of views is done by the construction of cooperative parallel composition of graph transformation systems, developed by Leila Ribeiro and presented at the same seminar. If the specification is complete, a view may describe an observation of the system in operation. In this case we speak of a user view. It turns out that the semantics of such a view cannot be described by computations (i.e., graph transformations), but just by observations of computations of the global system. Such observations of computations cannot be represented by graph transformations in the usual sense because a local view may lack operations (productions) of the global system, so that state changes may be observed that do not have a cause in the local view. Therefore, the notion of graph transition is introduced as loose semantics for productions, where the production specifies only a lower bound to the activities that are to happen during application. Contrastingly, in the classical doublepushout approach to graph rewriting, productions are interpreted as complete descriptions of the transformations to be performed. For typed graph transformation systems a transition sequence semantics is developed, comprising all finite and infinite sequences of transitions in a system. Moreover, this semantics is shown to be compositional w.r.t. the synchronization of views.

Behavioral Constraints for Loose Graph Transformation Systems - Heckel, Reiko (Report on the Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)

Industrial maintenance modelled in SOCCA: an experience report - de Bunje, Tineke; Engels, Gregor; Groenewegen, Luuk; Matsinger, Aart; Rijnbeek, Martin (Proceedings of the Fourth International Conference on the Software Process (ICSP 1996), Brighton (UK))
A large industrial process, software maintenance, has been modelled by using the process modelling language SOCCA. The paper reports about the experiences with this trial. In particular, feasibility, expressiveness, quality and the overall benefits of a formal SOCCA model are discussed and compared to the formerly existing informal process description. In order to illustrate the results, a well chosen process model fragment from the larger model is outlined in detail. It addresses in particular the human-intensive cooperation within the process and shows the seamless combination of technical components and human agent components in the SOCCA model. The main conclusions from this trial are that formal SOCCA models are suited to model realistic industrial processes and that due to an intrinsic modular structure of a SOCCA model, even huge models remain reasonably readable and understandable

A View-Based Approach to System Modelling - Engels, Gregor; Ehrig, Hartmut; Heckel, Reiko; Taentzer, Gabriele; Corradini, Andrea (Report on Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)
In order to manage the complexity of large system specifications, they have to be decomposed into subspecifications. Each subspecification describes a certain part of the system. This might be a certain aspect, like the data, dynamic, or functional aspect, as it is known from object-oriented modelling techniques. Or it might be a certain view onto the system, as it is known from database modelling techniques. The talk motivates the usage of views in graph grammarbased specifications. First, the usage of typed graph grammars inherently ensures an integration of the data and the functional aspect within a view. Second, it is explained that it is not appropriate in case of views to have a fixed semantics. The standard fixed semantics, i.e. a graph transformation system, has to be relaxed to a loose semantics, i.e. a graph transition system. This reflects the idea that a view models only a part of the complete system. Other views may overlap a view with respect to data or functionality. A complete system specification is yielded by exploiting the approach of cooperative parallel composition of graph grammars (see talk by Leila Ribeiro).

Object-oriented specification of coordinated collaboration - Engels, Gregor; Groenewegen, Luuk; Kappel, Gerti (Proceedings of IFIP World Conference on IT Tools (1996), Canberra (Australia))
Object-oriented specification mechanisms have become famous for modelling structure and behaviour together in terms of autonomous objects communicating via message passing. However, whereas most object-oriented specification methods are strong in modelling the local behaviour of single objects, they fall short on modelling the coordinated behaviour and collaboration of several objects together The aim of this paper is to contribute to fill this gap. The paper reports on concepts, language constructs, and experiences with three collaboration formalisms in the area of object-oriented specifications.